Blanket stories and blurring binaries: contemporary Native American art and the discourse of authorship - Swanson, Katherine E. (My University, 2023)
This thesis explores the relationship between Native American art and the recent rise in participatory art. In this thesis I question the precedents for the subversion of single authorship and collective creation, how Native American artists assert and articulate indigenous epistemologies through contemporary practices, and what form it takes when Native artists internalize Euro-American artistic practices and blur the influences between indigenous and Western backgrounds. The current discourse on participatory art and social engagement construes it as an unprecedented phenomenon, which fails to take into account intercultural exchange between Western art and art from other cultural traditions. I argue that contemporary participatory art and traditional Native American art share a subversion of the solo artist and invoke contemporary Native participatory artists to demonstrate how the lack of a Great Artist tradition allows for more fluid--authorship in order to destabilize the binary opposition between collective and individual artistic production. This fluid authorship also articulates visual sovereignty for contemporary Native artists who are free to explore more traditional artistic practices. This thesis seeks to locate contemporary Native American art within a broader global contemporary context by investigating how cross-cultural exchange shapes contemporary art.
M.A. in Art History--University of Oklahoma, 2015
Includes bibliographical references.
Keywords: Indian art--North America; Interactive art